IMPLEMENTATION OF STATE POLICY IN THE FIELD OF SUBSIDIZING INDUSTRIAL ENTERPRISES - F. M. Ibyatov; M. A. Machul’skii (Вестник университета, 2020)
The state policy of the Russian Federation in the field of development of industrial enterprises has been studied. The analysis of the share of industry in the in the gross domestic product of the Russian Federation for 2014–2018 has been carried out. Russia is ranked 4th in the ranking of countries in terms of purchasing power parity, a significant position is granted to industrial production in this case. Despite this situation, industrial sector of Russia is characterized by the presence of negative trends, the elimination of which is crucial. In order to eliminate negative trends, investment programs aimed at supporting the development of industry are being implemented in Russia. Budgetary allocations are particularly important in supporting Russian industrial production. The resuts of the analysis of the dynamics of budget allocations indicate their increase in recent years. The dynamics of labor productivity in the industrial sector, as well as the main indicators of production have been analysed.